2011
DOI: 10.1371/journal.pone.0020214
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Neointima Formation Following Arterial Injury in Immune Deficient Rag-1−/− Mice Is Attenuated by Adoptive Transfer of CD8+ T cells

Abstract: T cells modulate neointima formation after arterial injury but the specific T cell population that is activated in response to arterial injury remains unknown. The objective of the study was to identify the T cell populations that are activated and modulate neointimal thickening after arterial injury in mice. Arterial injury in wild type C57Bl6 mice resulted in T cell activation characterized by increased CD4+CD44hi and CD8+CD44hi T cells in the lymph nodes and spleens. Splenic CD8+CD25+ T cells and CD8+CD28+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
50
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(59 citation statements)
references
References 40 publications
7
50
1
1
Order By: Relevance
“…Increased IP-10 levels have been associated with rapid disease progression in acute HIV-infection 40 and with immunologic treatment failure following ART initiation 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Increased IP-10 levels have been associated with rapid disease progression in acute HIV-infection 40 and with immunologic treatment failure following ART initiation 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Our colocalization studies also identified TUNEL + apoptotic endothelial cells and smooth muscle cells including those in the fibrous cap. CD8 + T lymphocytes are cytolytic to human endothelial cells 5 and smooth muscle cells in injured arteries 6 and also cytotoxic to these cells in vivo. 35 In programmed cell death-1-deficient Ldlr −/− mice, increased CD8 + T cells in the lesions were also associated with more apoptotic cells comprising both smooth muscle cells and nonsmooth muscle.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that this observation is related to the protection of the young vascular wall against chronic inflammation and NIH. Dimayuga et al (6) found that adoptive transfer of CD8 ϩ T cells inhibited neointima formation in mice after arterial injury.…”
Section: Discussionmentioning
confidence: 99%